Geometric Properties of a New Integral Operator - Roberta Bucur; Loriana Andrei; Daniel Breaz (Abstract and Applied Analysis)
We obtain sufficient conditions for the univalence, starlikeness, and convexity of a new integral operator defined on the space of normalized analytic functions in the open unit disk. Some subordination results for the new integral operator are also given. Several corollaries follow as special cases.